The Impact of Preference Signaling on Interview Invitations and Match Outcomes in the 2023 to 2024 Orthopaedic Residency Cycle - Samir Alkhouri, BS, MBA; Matthew Michelberger, BS; Jay Parikh, BS; Christopher J. Fang, MD; Cameron Harris, MD; Karen Nelson, DO; Sukanta Maitra, MD; Brock Wentz, MD (JBJS Open Access)
Background:. Orthopaedic surgery is among the most competitive residency specialties with recent cycles seeing record application volumes and declining match rates. Therefore, the aim of this study was to examine the Electronic Residency Application Service (ERAS) signaling system's impact on interview invitations and outcomes in the 2023 to 2024 orthopaedic surgery residency application cycle, building on data from its inaugural use. Methods:. Application and interview data were collected from official National Resident Matching Program reports, Association of American Medical Colleges (AAMC) Supplemental ERAS Application Report, and specialty-wide surveys. Statistical findings, including interview distributions and match rates, were extracted from previously published studies and AAMC database. Results:. The 2023 to 2024 cycle had 1,492 applicants. On average, applicants submitted 86 applications (range: 12-198), with the majority submitting between 70 and 80 applications. Nearly all orthopaedic applicants (∼97%) participated in preference signaling. Applicants received more interview invitations from programs they signaled than from programs not signaled. Signaled programs accounted for the majority (∼79%) of interview offers. Only 19% to 20% of interview offers were extended by programs that applicants did not signal. Of matched applicants, the majority (90%) matched at a program they had signaled, and the remaining (10%) matched at programs, they did not signal. Furthermore, the majority of applicants (63%) who matched were matched at programs where they had completed an away rotation. Although signaling aimed to reduce excessive applications, the overall volume per applicant remained high. While 45% of applicants reported feeling incentivized to apply more selectively, many still submitted broad applications. Conclusions:. Preference signaling in orthopaedic surgery residency applications has markedly reshaped the match landscape by concentrating interview opportunities and match success predominantly within signaled programs. The authors recommend that medical students strategically research and prioritize programs when signaling, while residency programs should continue refining how they interpret signals to enhance holistic and equitable selection processes.